2009
DOI: 10.1007/s00059-009-3316-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Chronic Heart Failure

Abstract: Cardiac biomarkers are very important in diagnosis, risk stratification, and management of patients with heart failure. Although not meeting all criteria for an ideal biomarker, natriuretic peptides primarily have a diagnostic and prognostic role. Other routinely available and newly emerging biomarkers have a complementary role in patient management; thus multimarker strategy might be warranted in future. The quest for a single marker or a combination is ongoing and several established, widely available biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 56 publications
1
13
0
2
Order By: Relevance
“…Many studies have shown that factors such as the inflammatory status, poor nutritional state and, obviously, the extent of cardiac dysfunction herald a poor prognosis in CHF [7][8][9][10][11][12][13]. However, none of these conventional indicators and, interestingly, also not LVF or RVF, carried any prognostic potential in our patient group.…”
Section: Discussionmentioning
confidence: 59%
“…Many studies have shown that factors such as the inflammatory status, poor nutritional state and, obviously, the extent of cardiac dysfunction herald a poor prognosis in CHF [7][8][9][10][11][12][13]. However, none of these conventional indicators and, interestingly, also not LVF or RVF, carried any prognostic potential in our patient group.…”
Section: Discussionmentioning
confidence: 59%
“…Similar to several other biomarkers [4,5], increased circulating levels of pro-inflammatory cytokines have been shown to be closely related to the worsening of the patients' clinical symptoms and to predict poor short- [6] and long-term survival [7,8].…”
Section: Role Of Cytokines In Chronic Heart Failurementioning
confidence: 96%
“…Nonetheless, we detected cytoplasmatic proteins, which are involved in relevant pathological processes. Troponin T has been demonstrates as most reliable to detect and estimate the extent of cardiac damage [37]. Apolipoprotein E, tropomyosins, alpha-2 macroglobulin, complement 3, creatin kinase B and ceruloplasmin have been also described as biomarkers for chronic heart failure [38][42].…”
Section: Discussionmentioning
confidence: 99%